Lightning risk assessment for hall building based on Malaysian standard MS IEC: article / Mohd Amzar M. Amin - M. Amin, Mohd Amzar (Universiti Teknologi MARA (UiTM), 2013)
On January 2006, Malaysia adopted lEC Standard as Malaysian Standard IEC 62305·2:2006, Protection against Lightning Part 2: Risk management which applies to the risk assessment of building and public facilities. This paper based on Malaysian standards assesses risks of lightning strike to Examination Hall which is Dewan Sri Budiman UiTM Shah Alam, Malaysia for the application of the new Malaysian standards for reference. In this paper, carries out data collection and zoning on the hall as well as the lightning risk assessment according to the evaluation process and method. Comparing all the achievement Lightning risk values with reference value results of the assessment. Finally it makes the recommendation needed with lightning protection of hall building.